Promoting Covid-19 vaccination with Instagram - Fahmi, Ahmad Maulanal; Azizah, Hanifah Nur; Mahendra , I Putu Arda; Fatkhiatin , Irma; Hammad, Jehad A.H (Association for Scientific Computing Electrical and Engineering, 2021)
The COVID-19 Vaccination Program is essential information during this pandemic. Information about COVID-19 vaccination is disseminated through social media, one of which is Instagram. During the COVID-19 pandemic, the Ministry of Health's Instagram accounts in various countries provided much information about COVID-19, including vaccinations. This research was made to determine the role of Instagram as a media to promote the invitation to vaccinate for COVID-19 by using the calculation of engagement rates in each post category on the Instagram account of the Ministry of Health of Indonesia, Malaysia, the United States, and Australia. The results obtained in this study are that these accounts have implemented the right strategy in COVID-19 vaccination, and several strategic refinements need to be done.